The relationship between overall quality, internet usage, user satisfaction, task-technology fit, and performance impact among employees within public sector in Yemen / Osama Mutahar Ahmed Isaac - Ahmed Isaac, Osama Mutahar (Institute of Graduate Studies, UiTM, 2018)
The internet/World Wide Web (WWW) has become increasingly indispensable in the daily life of most individuals and has significantly impacted every facet of operations in organizations. It is, therefore, critical to understand its actual use in an organization because of its facility to be a platform for knowledge management and capability to transform knowledge acquisition, improve task efficiency, enhance communication quality, and strengthen decision quality. Yet, despite its importance and world-wide reach, internet usage in Yemen is one of the lowest among the world's countries. Organizations around the world are looking for the development and keep up to date with emerging technology. One of the sectors that are affected by the growth of Internet technology is the public sector. Many researchers have studied and proposed theories and models of technology usage in order to predict and explain user behavior with technology to account for the rapid change in both technologies and their environments. Based on three well-known topic in information technology; Technology Acceptance, Task-Technology Fit and Information Systems Success within five well-known theories and models (TAM, UTAUT, TTF, DMISM and Wang & Lai model), this study developed and validated a multi-dimensional model, Quality of Technology Usage Model (QTUM), to better understand internet usage among employees within public sector from an integrated perspective of technological, individual, social and organizational. Furthermore, proposed and validated two second-order Models within the full model; overall quality which contains seven first-order constructs (system quality, information quality, service quality, task quality, individual quality, social quality and top management quality) and performance impact which contains four first-order constructs ( process, knowledge acquisition, communication quality and decision quality). A survey questionnaire was used to collect primary data from 530 employees within all thirty government ministries-institutions in Yemen. The data analysis start with initial exploratory factor analysis (EFA), followed by confirmatory factor analysis (CFA) and lastly structural equation modelling (SEM) via AMOS…